Timon of Athens (1606?) and Timon (1602?): Rhetorical and Ritualistic Violence - Orman, Steve (Studia Anglica Posnaniensia, 2013)
This article seeks to explore representations of theatrical anger in William Shakespeare and Thomas Middleton’s Timon of Athens (1606?) and a play written by students from one of the Inns of Court, the Inner Temple, entitled Timon, written and performed at the Inn circa 1602. The article is concerned with two types of violence exhibited in both plays; rhetorical violence and ritualistic violence. Early modern rhetorical violence is self-consciously performative and manipulative compared to ritualistic violence which is unbridled and emasculating; a bodily performance that cannot be controlled via self-regulation. By exploring cultural perceptions of anger, this article attempts to account for the range of violence performed by the two Timons.